Biomechanical impact analysis of implant positioning in lumbar interbody fusion by the finite element method - Ho, Le Duy Nguyen; Le, Thi Hoang Thuy; Dang, Thuc Tri; Vu, Truc Tam; Thien, Truong Tich (Vietnam Journal of Science and Technology, 2026)
Transforaminal Lumbar Interbody Fusion (TLIF) is a fusion technique in spinal surgeries reserved for chronic conditions requiring stabilization e.g. lumbar spinal stenosis and spondylolisthesis, especially when conservative treatments fail. The procedure involves removing the pathological disc material and putting a spacer with morselized bone graft in the disc space via the transforaminal pathway in order to promote interbody bony fusion. The whole construction is stabilized posteriorly by pedicle screw fixation. However, the conventional TLIF technique possessed several drawbacks including cage subsidence and cage protrusion, due to the posterior position of the cage within the disc space and modifications have been proposed in the effort to reduce the mentioned problems. Selecting pedicle screw length is also a topic to debate, when no clear consensus has been established regarding that matter. Therefore, this study uses Finite Element (FE) model under physiological axial compression to investigate the screw length and cage positioning effects on the bone and instruments. This model accounts for the structural interactions between the cage, pedicle screws, and surrounding bone tissue. Our findings highlight the novel insight that anterior cage placement reduces the risk of cage subsidence and improves load distribution. Additionally, the study demonstrates that screw tips should extend beyond the center of the cage to enhance load transfer efficiency and reduce stress on the fixation system.